Synta-Pragmatics of The Conjunctions in Kurdish Language - Rasoul, Salah H.; Kareem, Omar M. (KOYA UNIVERSITY JOURNAL OF HUMANITIES AND SOCIAL SCIENCES, 2019)
The title of this research is (The Syntax-Pragmatics of the Conjunctions in Kurdish Language). The conjunctions have a great role in language by connecting between words, phrases and sentences. They also have a significant role in deletion of reduction extra elements. These are some examples of them in Kurdish; ‘belam, û, belku, ne…ne, keçî, and so on’. They have a great role in clarifying the aims of the speaker and its ideas. The study consists of two main parts and the bibliography. In the first part of the research, the syntactical role of the conjunctions is shown. Furthermore, the places of the conjunctions in compound sentences are explained. According to the Kurdish language grammatical rules, there is not a specified gap for the conjunctions, and their places are changeable within compound sentences. Besides that, compound sentences also categorized according their dual or multi branches. Each part of the compound sentences have its importance, and their level are not same. The second part of the research deals with the pragmatics role of the conjunction. The focus is on the new meaning that are made in collocation with other parts of the sentence to send the message of the speaker. This is because their meaning is very related with the context. Eventually, the conclusion is drawn.